Spillover Beliefs between Health and Pro-Environmental Behaviours - Valentina Giovanna Bancale; Pierre Gérain; Dimitri Van Ryckeghem; Ann DeSmet (European Journal of Health Communication (EJHC))
Health and environment are closely related. These interrelationships are conceptualised within the framing of planetary health. Targeting health and pro-environmental behaviours (PEB) together is of growing interest. To enhance the effectiveness of joint interventions on multiple health and PEB, this study aimed to (1) explore whether behaviours are believed to facilitate (positive spillover) or conflict (negative spillover) with each other and assess (2) predictors of these spillover beliefs. A cross-sectional survey was administered to 311 adult participants (Mage = 29.2, SD = 9.8; 50% female) from Western Europe. A scale was developed to measure spillover beliefs. Self-reported values, health and green identity, as well as self-efficacy, pride, and guilt related to specific health and PEB were assessed as predictors. Results showed that 23.2% and 4.8% of participants respectively agreed with positive (M = 3.0, SD = 0.8) and negative (M = 2.2, SD =0.7) spillover beliefs. Personal values, health and green identity, as well as self-efficacy and guilt for PEB, significantly predicted both types of spillover beliefs. Pride for PEB increased the likelihood of positive spillover beliefs; self-efficacy, pride and guilt for health did not. These findings on spillover beliefs support further investigation of spillover within the planetary health context.